2013
DOI: 10.1007/s00018-013-1528-5
|View full text |Cite
|
Sign up to set email alerts
|

A PAK6–IQGAP1 complex promotes disassembly of cell–cell adhesions

Abstract: p-21 activated 6 (PAK6), first identified as interacting with the androgen receptor (AR), is over-expressed in multiple cancer tissues and has been linked to the progression of prostate cancer, however little is known about PAK6 function in the absence of AR signaling. We report here that PAK6 is specifically required for carcinoma cell–cell dissociation downstream of hepatocyte growth factor (HGF) for both DU145 prostate cancer and HT29 colon cancer cells. Moreover, PAK6 overexpression can drive cells to esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…To investigate how PAK6 targets to cell-cell adhesions, we first confirmed that we could observe PAK6 at E-cadherin-rich cell-cell contacts as previously reported (Fram et al, 2014). Using lentiviral infection, we generated stable DU145 prostate cancer cell lines expressing GFP or GFP-PAK6.…”
Section: Pak6 Targets To Cell-cell Adhesionssupporting
confidence: 74%
See 2 more Smart Citations
“…To investigate how PAK6 targets to cell-cell adhesions, we first confirmed that we could observe PAK6 at E-cadherin-rich cell-cell contacts as previously reported (Fram et al, 2014). Using lentiviral infection, we generated stable DU145 prostate cancer cell lines expressing GFP or GFP-PAK6.…”
Section: Pak6 Targets To Cell-cell Adhesionssupporting
confidence: 74%
“…Until recently, little was known about the basic cellular role of PAK6 other than its interaction with and phosphorylation of androgen receptor (Yang et al, 2001;Jaffer and Chernoff, 2002;Schrantz et al, 2004;Liu et al, 2013). However, last year, PAK6 was shown to localize to cell-cell adhesions in DU145 prostate cancer cells (Fram et al, 2014). The mechanism of targeting and its isoform specificity were not explored, but PAK6 was shown to promote the disassembly of cell-cell adhesions (Fram et al, 2014), a crucial step in epithelial-to-mesenchymal transition, one of the hallmarks of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies has demonstrated that Cdc42 regulates the apical junction formation in human bronchial epithelial cells through PAK4 32 . PAK6, which was initially identified to be an androgen receptor protein, and has recently be reported to be involved in cell: cell dissociation in response to HGF, independent of androgen receptor (AR) signalling 33 and is thought to drive colony escape 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, a complex of PAK6/E-cadherin/IQGAP1 was identified as the cells dissociate in response to HGF 35 . Group 2 member PAK5 has been shown to interact with p120-Catenin, an important component of the cadherin-catenin-complex at adherens junctions 36 .…”
Section: Introductionmentioning
confidence: 99%